MiR-1284 suppresses the proliferation and migration of thyroid cancer: MiR-1284 suppresses the development of thyroid cancer - Zhang, Lingjie; Ge, Rui; Cheng, Aiqun; Hu, Tianhua (Cellular and Molecular Biology, 2023)
To elucidate the role of microRNA-1284 (miR-1284) in the onset of thyroid cancer (TC) and its underlying mechanism. Differential expressions of miR-1284 in TC and thyroid tissues were detected. Regulatory effects of miR-1284 on proliferative, migratory, apoptotic potentials and cell cycle progression were assessed. In addition, miR-1284 levels in TC tissues and peripheral blood of TC patients were determined as well. Through collecting culture medium and exosomes of PTC cells, changes in miR-1284 levels were examined. MiR-1284 was downregulated in TC than normal thyroid tissues. Overexpression of miR-1284 attenuated proliferative and migratory potentials, but induced apoptosis in TPC-1 and FTC-133 cells. Moreover, overexpression of miR-1284 upregulated E-cadherin and downregulated N-cadherin in papillary TC (PTC) cells. MiR-1284 was downregulated in TC tissues, while its level in the peripheral blood of TC patients was upregulated. Besides, miR-1284 was upregulated in the culture medium and exosomes of PTC cells, which was reversed by Brefeldin A treatment. Overexpression of miR-1284 suppresses proliferative and migratory potentials and induces apoptosis in TC. Upregulated miR-1284 in the peripheral blood of TC patients may be derived from exosomes secreted by PTC cells.